Hospital Admission to a Window-Side Bed Does Not Prevent Delirium: A Retrospective Cohort Study of Older Medical Inpatients in General Wards - Aomura, Daiki; Yamada, Yosuke; Harada, Makoto; Hashimoto, Koji; Kamijo, Yuji (Frontiers in Medicine, 2021)
Background- Delirium in older inpatients is a serious problem. The presence of a window in the intensive care unit has been reported to improve delirium. However, no study has investigated whether window-side bed placement is also effective for delirium prevention in a general ward. Objectives- Clarify the association between admission to a window-side bed and delirium development in older patients in a general ward. Design- Retrospective cohort study of older patients admitted to the internal medicine departments of Shinshu University Hospital, Japan. Participants- The inclusion criteria were the following: 1) admitted to hospital internal medicine departments between April 2009 and December 2018, 2) older than 75 years, 3) admitted to a multi-patient room in a general ward, and 4) unplanned admission. The number of eligible patients was 1556. Exposure- Comparison of 495 patients assigned to a window-side bed (window group) with 1061 patients assigned to a non-window-side bed (non-window group). When patients were transferred to the other type bed after admission, observation was censored. Main Measures- The main outcome of interest was “delirium with event” (e.g., the use of medication or physical restraint for delirium) within 14 days after admission as surveyed by medical chart review in a blinded manner. Key Results- The patients had a median age of 80.0 years and 38.1% were female. The main outcome was recorded in 36 patients in the window group (10.7 per thousand person-days) and 84 in the non-window group (11.7 per thousand person-days). Log-rank testing showed no significant difference between the groups (p=0.78). Multivariate analysis with Cox regression modeling also revealed no significant association for the window group with main outcome development (adjusted hazard ratio 0.90, 95% confidence interval 0.61 to 1.34). Conclusions- Admission to a window-side bed did not prevent delirium development in older patients admitted to a general ward.